SOCIAL DISCRIMINATION IN MICHAEL LEMBECK THE CLIQUE MOVIE (2008): MARXIST CRITICISM - SARTINI , SARTINI (2011)
SARTINI. A. 320 070 087. SOCIAL DISCRIMINATION IN MICHAEL LEMBECK THE CLIQUE MOVIE (2008): MARXIST CRITICISM RESEARCH PAPER. SCHOOL OF TEACHER TRAINING AND EDUCATION MUHAMMADIYAH UNIVERSITY OF SURAKARTA. 2011. The object of the study is a movie The Clique directed by Michael Lembeck. The study is about social discrimination between Messei and Claire directed by Michael Lembeck published in 2008. The objective of the study is to analyze the structural elements in the movie and to analyze women emancipation of the movie based on feminist approach. The researcher employs the descriptive qualitative research as a type of the research. The data sources are divided into two, namely primary data source and secondary data source. The primary data source is the events of the movie and script of The Clique and the secondary data source is biography of character. The method of collecting data is documentation. The technique of analyzing data is descriptive. The result of the study is as follows; First, based on the structural analysis, Michael Lembeck delivers a moral message that human being are more than their economic status. Second, based on the Marxist analysis, Michael Lembeck reflects that upper class ad lower class are equal.